The Effectiveness of the Complete Sentence Learning Method with Giving Questions and Getting Answers on Students' Physics Learning Outcomes of SMPN 1 Sampaga - Imam Permana; Fitriani Kadir; muh Subhan; I Gede Purwana Edi Saputra; Syamsuriana Basri (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
This study aims to determine the increase in physics learning outcomes after combining the Complete Sentence learning method with Giving Questions and Getting Answers to class VIII students of SMPN 1 Sampaga Kab. Mamuju. This type of research is Pre-Experimental Design with One-Group Pretest-Postest Design. The population of this study was all class VIII students of SMPN 1 Sampaga for the 2019/2020 academic year. The sample was determined using the Simple Random Sampling technique. The research instrument used was the learning achievement test instrument and student observation. The data analysis technique used is descriptive and inferential statistical data analysis. The results of the study of student learning outcomes data before using the combination of the Complete Sentence learning method with Giving Questions and Getting Answers reached an average value of 40.18. The Ministry of Education and Culture guidelines regarding the category of students' cognitive outcomes show the most significant percentage in the low sort, which is equal to 60.71%. Combining the Complete Sentence learning method with Giving Questions and Getting Answers achieves an average score of 75.54. The Ministry of Education and Culture guidelines regarding the categories of students' cognitive outcomes, which show the most significant percentage, are established in the high class, which is equal to 50.00%. The results of hypothesis testing using the t-test, H0 is rejected, and Ha is accepted. This study concludes that this learning method effectively improves student learning outcomes in Work and energy. This research implies that applying a combination of the Complete Sentence learning method with Giving Questions and Getting Answers deserves to be considered a physics learning method in improving learning outcomes.